Kindlin-2 (Mig-2): a co-activator of β(3) integrins - Ma, Yan-Qing (The Rockefeller University Press, 2008)
Integrin activation is essential for dynamically linking the extracellular environment and cytoskeletal/signaling networks. Activation is controlled by integrins' short cytoplasmic tails (CTs). It is widely accepted that the head domain of talin (talin-H) can mediate integrin activation by binding to two sites in integrin β's CT; in integrin β(3) this is an NPLY(747) motif and the membrane-proximal region. Here, we show that the C-terminal region of integrin β(3) CT, composed of a conserved TS(752)T region and NITY(759) motif, supports integrin activation by binding to a cytosolic binding partner, kindlin-2, a widely distributed PTB domain protein. Co-transfection of kindlin-2 with talin-H results in a synergistic enhancement of integrin α(IIb)β(3) activation. Furthermore, siRNA knockdown of endogenous kindlin-2 impairs talin-induced α(IIb)β(3) activation in transfected CHO cells and blunts α(v)β(3)-mediated adhesion and migration of endothelial cells. Our results thus identify kindlin-2 as a novel regulator of integrin activation; it functions as a coactivator.